2006
DOI: 10.1086/503331
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Traits: A New Statistical Model to Separate Within‐ and Between‐Individual Effects

Abstract: Evolutionary questions regarding aging address patterns of within-individual change in traits during a lifetime. However, most studies report associations between age and, for example, reproduction based on cross-sectional comparisons, which may be confounded with progressive changes in phenotypic population composition. Unbiased estimation of patterns of age-dependent reproduction (or other traits) requires disentanglement of within-individual change (improvement, senescence) and between-individual change (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
416
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(435 citation statements)
references
References 23 publications
7
416
1
Order By: Relevance
“…when taking individual heterogeneity into account or not). Moreover, including the age at last reproduction, to take into account the selective disappearance of low-quality individuals (as suggested in Van de Pol & Verhulst 2006), did not affect our results (results not presented). This indicates that, in contrast to large herbivores ( Nussey et al 2008), the variation in individual quality and viability selection is not a major issue in our red squirrel population.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…when taking individual heterogeneity into account or not). Moreover, including the age at last reproduction, to take into account the selective disappearance of low-quality individuals (as suggested in Van de Pol & Verhulst 2006), did not affect our results (results not presented). This indicates that, in contrast to large herbivores ( Nussey et al 2008), the variation in individual quality and viability selection is not a major issue in our red squirrel population.…”
Section: Discussionmentioning
confidence: 73%
“…A variety of genetic, maternal and environmental factors can lead to variation among individuals within a population. For example, in the Kluane red squirrel population, it has been shown that the individual traits vary with territory quality (LaMontagne 2007), year of birth (Descamps et al 2008b) or characteristics of the mothers (McAdam et al 2002;Descamps et al 2008a) Such individual heterogeneity has to be accounted for when studying trade-offs and/or age-specific change in the life-history traits ( Vaupel & Yashin 1985;Cam et al 2002;Van de Pol & Verhulst 2006;Nussey et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if variation seen in the timing of breeding within the population was owing to differences between individuals or owing to within-individual responses to frequency of rainfall, a methodology known as 'within-subject centring' was used [27,28]. Hence, a second model was constructed with two new predictor variables derived to describe the between-subject variance (b b ) and within-subject variance (b w ).…”
Section: Methods (A) Study Population and Datamentioning
confidence: 99%
“…We included an interaction between ROS utero and both age and its square to determine whether reproductive senescence differed in relation to early-life environment. Age at last observation was also included as fixed effect term to control to for selective disappearance (the non-random departure from the dataset of individuals as age increase) so that age effect reflected an unbiased estimate of within-individual change [52]. Age at last observation was retained in the model independent of its statistical significance.…”
Section: (D) Statistical Analysesmentioning
confidence: 99%